2020
DOI: 10.5005/jp-journals-10024-2729
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-related Knowledge and Assessment of Oral Health Status of Diabetic Patients Attending Dental Clinic at College of Dentistry, Hail, Kingdom of Saudi Arabia

Abstract: Aim:This study was aimed to evaluate the oral health status and knowledge of diabetic and nondiabetic patients attending dental clinic at College of Dentistry, Hail, the Kingdom of Saudi Arabia. Materials and methods: It was an observational cross-sectional study. Using nonprobability convenient sampling technique, data were collected from 202 respondents. A total of 202 diabetic and nondiabetic patients were screened for the study. Data were collected by interview using the structured, self-administered quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…One study from Madinah assessing the prevalence of dental caries in young women found that diabetic females were more likely to have carious lesions (21). Similarly, a study from Hail noted that prevalence rates of plaque were higher in DM patients than those without DM (16). Yet another study conducted at a hospital's diabetes unit in Riyadh showed a positive correlation between DM and periodontal health via reporting of plaque index which concluded that Saudi patients with chronic, uncontrolled blood sugar levels were more likely to have higher amount of calculus deposits and higher susceptibility of periodontitis (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study from Madinah assessing the prevalence of dental caries in young women found that diabetic females were more likely to have carious lesions (21). Similarly, a study from Hail noted that prevalence rates of plaque were higher in DM patients than those without DM (16). Yet another study conducted at a hospital's diabetes unit in Riyadh showed a positive correlation between DM and periodontal health via reporting of plaque index which concluded that Saudi patients with chronic, uncontrolled blood sugar levels were more likely to have higher amount of calculus deposits and higher susceptibility of periodontitis (22).…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted in Hail in a cohort of dental patients at a university hospital clinic showed that the majority of the patients has general awareness of the dental problems associated with DM (16). But the bulk of these participants had failed to convey to the attending dental practitioner their diabetes status thereby showing a lack of awareness regarding the importance of reporting their diabetes history to the dental professionals for effective management of their condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tandem with the low levels of oral health advice and information received, some studies identified that participants were receptive to receiving more oral health promotion information from health care providers, primarily doctors and dentists. In a Saudi Arabian study, Mian et al [ 63 ] similarly found that up to 81% of people who had diabetes had never spoken to their doctor or dentist about oral health. An Australian survey also identified that 90% of people with diabetes did not receive oral health information [ 61 ] suggesting that the role of oral health promotion among non-dental care providers appears to be limited in other regions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected by an interviewer-administered (face to face interview) questionnaire. The questionnaire was composed of close-ended questions that were derived from two relevant previous studies in the same area [20,21]. The study tool adopted a simplified and modified English version questionnaire to accommodate the aim of this study.…”
Section: Methodsmentioning
confidence: 99%